2023
DOI: 10.3389/fmicb.2023.1132853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic fertilizers on yield, soil physico-chemical property, soil microbial community diversity and structure of Brassica rapa var. Chinensis

Abstract: The amount of chemical fertilizer for vegetables is on the high level in China. The use of organic fertilizers to meet the nutrient requirement of crops will be an inevitable practice in sustainable agriculture. In this study, we compared the effects of pig manure fertilizer, rabbit manure fertilizer and chemical fertilizer on yield, quality of Brassica rapa var. Chinensis, soil physico-chemical properties and microbial community by using two consecutive seasons of three fertilizers in a pot experiment. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Organic fertilizers can be obtained from agricultural waste, livestock manure, municipal waste, and sludge [2]. Organic fertilizers increase the waterholding capacity, microbial growth, and soil structure [8] [9]. The drawbacks of organic fertilizers are the unequal distribution of nutrients, slow release of nutrients, inconsistent product composition, and requirement in high quantities [8] [9].…”
Section: Organic Fertilizersmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic fertilizers can be obtained from agricultural waste, livestock manure, municipal waste, and sludge [2]. Organic fertilizers increase the waterholding capacity, microbial growth, and soil structure [8] [9]. The drawbacks of organic fertilizers are the unequal distribution of nutrients, slow release of nutrients, inconsistent product composition, and requirement in high quantities [8] [9].…”
Section: Organic Fertilizersmentioning
confidence: 99%
“…Organic fertilizers increase the waterholding capacity, microbial growth, and soil structure [8] [9]. The drawbacks of organic fertilizers are the unequal distribution of nutrients, slow release of nutrients, inconsistent product composition, and requirement in high quantities [8] [9]. Besides, the world is slowly moving towards organic fertilizers to overcome the environmental problems caused by chemical fertilizers such as soil acidification, soil pH change, the release of greenhouse gases, the release of heavy metals, and the destruction of beneficial species, which ultimately cause severe impact on human health [10] [11].…”
Section: Organic Fertilizersmentioning
confidence: 99%
“…Numerous researchers have reported that applying organic fertilizer not only leads to an increase in the plant height and individual weight of pakchoi but also results in elevated levels of essential components such as vitamin C, soluble sugars, and soluble proteins in pakchoi. Conversely, the application of organic fertilizer has been shown to reduce nitrate content [54][55][56]. The combined application of organic fertilizer with fresh water, brackish water, and magnetized-ionized brackish water irrigation had a substantial effect on the fresh weight, dry weight, and growth rate of pakchoi.…”
Section: Effects Of Combined Application Of Organic Fertilizer On Gro...mentioning
confidence: 99%
“…Rabbit manure can be used directly to fertilize crops 10 , 12 , 13 , as an ingredient in plant growth substrates 14 , 15 , as an adsorbent 16 , for biochar production 17 , 18 , and even in anaerobic fermentation to produce methane 19 .…”
Section: Introductionmentioning
confidence: 99%